Nicolas Baier : de la peinture par téléphone - Galland, Emmanuel (CV Photo, 2000)
(Free) arbiter, colourist, stain-ist, material-ist, collagist, designer (of interiors), assembler-operator—not to mention cameraman-editor—N.B. is a visual artist in the current sense of the term used for all French artists, whether they work small or great miracles. Nico is not a post-documentarist photographer (as the manipulations and stagings intrinsic to his projects affirm). He does not extend the parameters established by photo-sculpture, but produces according to the specialties of a contractor: inlayer-tiler.